Educational impact of an Augmented Reality (AR) application for teaching structural systems to non-engineering students. (October 2021) - Hu, Xinping; Goh, Yang Miang; Lin, Alexander
Abstract: This study evaluates the effectiveness of Augmented Reality (AR) in improving undergraduate non-engineering students' (n = 103) achievement of learning outcomes and their perception of AR as a learning tool. An AR application for teaching structural systems, Virtual and Augmented Reality for Structures (VARS), is developed and tested using a quasi-experiment and a questionnaire. The study shows that VARS AR significantly improves the posttest quiz score of the experimental group. In addition, a conceptual framework linking design considerations and achievement of learning outcomes is created. Based on the questionnaire survey, authentic context and user interface are important design considerations influencing students' perceived achievement of learning outcomes. It was found that experience using AR and background knowledge did not influence the perceived achievement of learning outcomes and change in quiz score.